2018
DOI: 10.2147/ott.s165262
|View full text |Cite
|
Sign up to set email alerts
|

Aloperine executes antitumor effects through the induction of apoptosis and cell cycle arrest in prostate cancer in vitro and in vivo

Abstract: BackgroundProstate cancer (PCa) is one of the most common malignant diseases among male patients. Although androgen deprivation therapy remains the main treatment for PCa, most patients would inevitably progress to castration-resistant PCa, which is the main cause of cancer-related deaths. Thus, novel antitumor agents are urgently needed. Recent studies demonstrated that aloperine (ALO) as a natural alkaloid showed antitumor effects in other cancer types. However, the biological function and underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…ALO inhibits proliferation, migration and invasion and induces apoptosis in human breast cancer cells [24]. ALO executes anti-tumor effects on prostate cancer through the induction of apoptosis and cell cycle arrest both in vitro and in vivo [15]. Our results showed that ALO inhibited the viability of bladder cancer cells cultured in hypoxia.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…ALO inhibits proliferation, migration and invasion and induces apoptosis in human breast cancer cells [24]. ALO executes anti-tumor effects on prostate cancer through the induction of apoptosis and cell cycle arrest both in vitro and in vivo [15]. Our results showed that ALO inhibited the viability of bladder cancer cells cultured in hypoxia.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, increasing experiments have confirmed the therapeutic potential of ALO in many kinds of diseases. Notably, ALO has been demonstrated to have therapeutic potential in various cancers, including thyroid cancer, breast cancer, prostate cancer, myeloma, hepatocellular carcinoma, glioma, and colon cancer [13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that miRNAs may negatively regulate gene expression by binding to the 3'-untranslated region (UTR) of target mRNAs to silence gene expression (9)(10)(11). It has been widely established that miRNAs serve critical roles in the regulation of several biological process, including proliferation, differentiation, apoptosis, tumorigenesis and metastasis (6,12,13). Furthermore, miRNAs may predict overall prognosis in certain types of cancer, including lung cancer (14), gastric cancer (15) and CRC (16).…”
Section: Introductionmentioning
confidence: 99%
“…Aloperine is extracted from the traditional Chinese medicine Sophora alopecuroides L., which possesses a variety of pharmacological activities such as anti-inflammatory, antifibrosis, anticancer, and antimicrobial [5]. Aloperine executes antitumor effects through the induction of apoptosis and cell cycle arrest in vitro and in vivo [6,7].…”
Section: Introductionmentioning
confidence: 99%